Integrated Metabolite Profiling and Network Pharmacology Reveal the Multitarget Therapeutic Potential of Curcuma amada Rhizome - Fatriani, Rizka; Istiadi, Khaerunissa Anbar; Khairani, Iffa Afiqa; Anisa, Hida Arliani Nur (Biotropika: Journal of Tropical Biology, 2026)
Curcuma amada Roxb. (mango ginger) is a medicinal plant traditionally known for its antioxidant, anti-inflammatory, and anticancer effects, however, the underlying molecular mechanisms are not fully understood. In this study, we combined metabolite profiling with in silico analysis (network pharmacology and molecular docking) to understand the bioactivity of C. amada. Gas chromatography-mass spectrometry (GC-MS) revealed a diverse metabolite composition with fifty-two compounds detected in the ethanol extract. Target prediction of the compounds was performed using SwissTargetPrediction, BindingDB, and ChEMBL. Hub genes were identified using Maximum Clique Centrality (MCC), which identified ESR1, PPARG, and NR3C1 as the main hub genes. Enrichment analysis showed a strong association with cancer-related pathways, particularly the PI3K–Akt signalling, endocrine resistance, and cell senescence pathways, as well as the biological processes regulating apoptosis, stress response, and intracellular signalling. Molecular docking studies of PPARG and ESR1 showed that the metabolites retinal, coronarin E, and 1H-cycloprop[e]azulene derivatives had stable binding affinities and interacted with residues in the ligand-binding domain (LBD) of the target proteins. Our findings suggest that C. amada exerts therapeutic effects through multiple mechanisms. Not a single molecule or pathway, but a coordinated network of metabolites acting on multiple targets. This integrative approach provides a scientific basis for the traditional use of C. amada and highlights its potential as a promising resource for drug discovery, particularly in the field of cancer therapy.